Myotonic dystrophy type 1 (DM1) clinical subtypes and CTCF site methylation status flanking the CTG expansion are mutant allele length-dependent - Morales Montero, Fernando (2021)
Myotonic dystrophy type 1 (DM1) is a complex disease with a wide spectrum of symptoms. The exact relationship between mutant CTG repeat expansion size and clinical outcome remains unclear. DM1 congenital patients (CDM) inherit the largest expanded alleles, which are associated with abnormal and increased DNA methylation f lanking the CTG repeat. However, DNA methylation at the DMPK locus remains understudied. Its relationship to DM1 clinical subtypes, expansion size and age-at-onset is not yet completely understood. Using pyrosequencing-based methylation analysis on 225 blood DNA samples from Costa Rican DM1 patients, we determined that the size of the estimated progenitor allele length (ePAL) is not only a good discriminator between CDM and non-CDM cases (with an estimated threshold at 653 CTG repeats), but also for all DM1 clinical subtypes. Secondly, increased methylation at both CTCF sites upstream and downstream of the expansion was almost exclusively present in CDM cases. Thirdly, levels of abnormal methylation were associated with clinical subtype, age and ePAL, with strong correlations between these variables. Fourthly, both ePAL and the intergenerational expansion size were significantly associated with methylation status. Finally, methylation status was associated with ePAL and maternal inheritance, with almost exclusively maternal transmission of CDM. In conclusion, increased DNA methylation at the CTCF sites f lanking the DM1 expansion could be linked to ePAL, and both increased methylation and the ePAL could be considered biomarkers for the CDM phenotype.